The Khoekhoegowab Personality Inventory: The Comparative Validity of a Locally Derived Measure of Traits - Thalmayer, Amber Gayle; Saucier, Gerard; Shino, Elizabeth N.; Job, Sylvanus (Frontiers in Psychology, 2021)
Objective: This study explores a personality inventory derived from the results of an indigenous lexical study of personality. From the 272 most commonly used personality descriptors in Khoekhoegowab, the most-spoken of extant Khoesan click languages of southern Africa, an 11-factor model of personality-trait structure was identified. Here, the Khoekhoegowab Personality Inventory (KPI) was created based on those results. Its psychometric properties, the convergent and divergent validity of its scales, and its incremental validity over Big Five and Six traits for predicting physical and mental health, religious practice and attitudes, and income are reported. Methods: Two to five key terms were selected for each of 10 KPI scales: Temperance, Prosocial Diligence, Gossip, Honesty/Morality, Temper, Implacability, Humility, Vanity, Resiliency vs. Agitation, and Courage vs. Fear. These 38 total items were administered to a large sample of adult speakers of Khoekhoegowab in Namibia (N = 632), together with five imported inventories translated into Khoekhoegowab: the 30-item Questionnaire Big Six (QB6), General Self-Reported Health, the Cascades Mental Health Assessment, the Satisfaction with Life Scale, the Duke Religion Index. The properties and intercorrelations of KPI subscales are explored, and their predictive ability for the other variables is compared to that of the QB6. Results: Due to the small number of items on each scale, poor internal consistency was anticipated, but the KPI scales' properties were somewhat better than those of the QB6. R-square change by the inventories as a whole, after accounting for age and gender, indicted that the KPI scales explained more variance than the QB6 scales in almost all criterion variables. Replication of established associations for Big Six traits was mixed: associations were largely as expected for Resiliency, Conscientiousness, and Honesty, but less so for Agreeableness and Extraversion. Conclusions: The KPI had some advantages over the QB6 in predicting physical and mental health. In particular, the four items of Resiliency vs. Agitation predicted lower scores on all physical and mental problem scales. Given psychological-care needs in Namibia, this might be used as a non-intrusive screener. Measurement challenges common to both surveys are discussed, possible solutions, and the utility of higher-order structures are discussed.